Hybrid meat products and co-creation: What do consumers say, feel and think? - Ryder, Chris; Jaworska, Sylvia; Grasso, Simona (Frontiers in Nutrition, 2023)
Introduction What consumers say about food and what kind of words they use to do so offers direct insights into their perceptions, preferences, reasoning, and emotions. Methods This study explores evaluations of hybrid meat products of 2,405 consumers from England, Denmark, and Spain. As part of a large survey, consumers were prompted to note down four words that come to mind when they read a description of a hybrid meat product, and then again after they were involved in a hypothetical co-creation task of a hybrid meat product. 18,697 words and phrases of language material was processed using computational corpus-based analysis and manual classification into semantic categories including: Evaluation, Sensory, Production, Emotion, Diets, Quality, Ethics, and Other. Results Consumers consider many dimensions when it comes to the evaluation of hybrid meat products including ethical conduct and sustainability. For all three languages, the number of positive words increased and the number of negative words decreased significantly (p < 0.001) following the co-creation task, suggesting that consumers see such products very positively once they are more familiar with them and know more about the ingredients. Subcategories that received most words include: taste, ingredients, healthiness, naturalness, innovation, and environment, implying that these areas are of most importance when it comes to the evaluation of hybrid meat products. The concept of nutrition (especially words pointing to positive aspects such as “rich in vitamins”, “nutritious”) also rose significantly in use after co-creation. Discussion The study reveals consumers’ vocabulary of hybrid meat products across the three countries and offers important insights for food producers to help them create innovative products that better align with consumers’ perceptions and expectations.